Correction: Directed evolution of gold nanoparticle delivery to cells. Issue 31 (3rd April 2020) - Li, Na; Larson, Timothy; Nguyen, Hong H.; Sokolov, Konstantin V.; Ellington, Andrew D.
Abstract : Correction for 'Directed evolution of gold nanoparticle delivery to cells' by Na Li et al., Chem. Commun., 2010, 46, 392–394.